Estimação estrutural de um modelo de busca por emprego com dispersão de produtividade: uma análise para o Brasil - Oliveira, Paulo Felipe Alencar de (2011)
The aim of this work is to estimate an equilibrium job search model with heterogeneity in productivities of firms using microdata from the Monthly Employment Survey (PME) collected in 2009. The model is estimated for the six metropolitan regions covered by the PME. Moreover,it is considered two mechanisms of wage determination: wage posting by monopsonistic firms and as a outcome of a Nash bilateral bargaining. To estimate the model, we use the non-parametric method developed by Bontemps, Robin and van den Berg (2000). There is a significant heterogeneity among the structural parameters estimated for the six metropolitan regions. Furthemore, the model with wage determination through bargaining show plausible results and not rejected by the data.